Optimizing the exhaust system to improve air quality in vehicle service repair shops - Hernanda Iqbal Zainul Muttaqin; RR Laksistya Rania Nur Prita Maira; Kurniawan Sigit Wahyudi (Journal of Automotive and Mechanical Applied Technology, 2025)
Air pollution from vehicle emissions, including NO₂, SO₂, O₃, TSP, and CO, negatively impacts workers' health and reduces work efficiency and productivity. This study aims to (1) develop an exhaust system at the Nissan Mlati ATPM workshop, and (2) determine the effectiveness of the exhaust system. The process of optimizing the exhaust system to improve air quality in the vehicle service repair stall was carried out through a comprehensive design and development project, including design and development phases and tool use. Then, metric volume (theoretical), actual use, and performance efficiency calculations were used. The results of the study show that optimizing the exhaust system at the Nissan Mlati ATPM workshop has been proven effective in increasing airflow capacity, maintaining air quality, and improving performance efficiency. This system can reduce the concentrations of pollutants such as Carbon Monoxide (CO) and Total Suspended Particulate (TSP) and increase workshop productivity without requiring structural design changes. The overall percentage results show a 51.03% increase in value after exhaust system optimization. This exhaust system not only improves air quality but also increases work productivity, which is crucial in the automotive industry's competition.